Estudio sobre la construcción discursiva de la imagen de China en los medios de comunicación principales de Perú: Un análisis basado en la cobertura sobre el Covid-19 - Chén, Zhi (Estudios Complutenses de Asia Oriental, 2025)
Studies on the image of China overseas have drawn great attention in academic circles, and the coverage of the COVID-19 by the overseas media is now significantly relevant to the construction of the national image of China. Under the theoretical framework of critical discourse analysis, this article uses corpus-based approach to describe and analyze the coverage of the COVID-19 in China by two main-stream media in Peru, in terms of the application of high frequency words, key words and modal verbs, which is intended to explore how the image of China is constructed in the news coverage discourse system and the reasons behind it. The studies show that, despite the slight difference in the points of focus, both Peruvian main-stream media have portrayed a positive image of China. We believe that the image is based on Peru’s cultural affinity with China, its deep economic ties with the former and the mutual political trust between these two countries.